2007
DOI: 10.1016/j.neuron.2007.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Spike-Timing Reliability Correlates with the Emergence of Fast Ripples in the Rat Epileptic Hippocampus

Abstract: Ripples are sharp-wave-associated field oscillations (100-300 Hz) recorded in the hippocampus during behavioral immobility and slow-wave sleep. In epileptic rats and humans, a different and faster oscillation (200-600 Hz), termed fast ripples, has been described. However, the basic mechanisms are unknown. Here, we propose that fast ripples emerge from a disorganized ripple pattern caused by unreliable firing in the epileptic hippocampus. Enhanced synaptic activity is responsible for the irregular bursting of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
279
5
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(305 citation statements)
references
References 52 publications
(93 reference statements)
20
279
5
1
Order By: Relevance
“…The shape and voltage depth profiles of pathological HFOs recorded in the dentate gyrus were similar to the shape and voltage depth profiles of population spikes evoked by perforant path stimulation . On the basis of these and other data it was hypothesized that pathological HFOs reflect spontaneous bursts of population spikes as a result of synchronous discharges of principal cells each of which fires at a lower frequency than the ensemble (Bikson et al, 2003a;Bragin et al, 2002aBragin et al, , 2007Foffani et al, 2007;Ibarz et al, 2010;Jiruska et al, 2010a). Areas generating pathological HFOs are not homogeneously distributed within brain areas and, on the basis of animal studies, a hypothesis was suggested that pathological HFOs are generated by pathologically interconnected neuron clusters or PIN clusters (Bragin et al, 2000(Bragin et al, , 2002a.…”
Section: Evidence For Hfos In Experimental and Clinical Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…The shape and voltage depth profiles of pathological HFOs recorded in the dentate gyrus were similar to the shape and voltage depth profiles of population spikes evoked by perforant path stimulation . On the basis of these and other data it was hypothesized that pathological HFOs reflect spontaneous bursts of population spikes as a result of synchronous discharges of principal cells each of which fires at a lower frequency than the ensemble (Bikson et al, 2003a;Bragin et al, 2002aBragin et al, , 2007Foffani et al, 2007;Ibarz et al, 2010;Jiruska et al, 2010a). Areas generating pathological HFOs are not homogeneously distributed within brain areas and, on the basis of animal studies, a hypothesis was suggested that pathological HFOs are generated by pathologically interconnected neuron clusters or PIN clusters (Bragin et al, 2000(Bragin et al, , 2002a.…”
Section: Evidence For Hfos In Experimental and Clinical Epilepsymentioning
confidence: 99%
“…However, a poor correlation between the firing frequency of individual cells and the dominant spectral peak in the local EEG confirms that fast ripples emerge as a network phenomenon and that single cells rarely fire faster than 400 Hz. This leads to the out-ofphase cluster hypothesis that suggest that independent pools of cells fire in concert but outof-phase with each other thus contributing to the higher frequency of fast ripples (Bikson et al, 2003a;D'Antuono et al, 2005;Foffani et al, 2007;Ibarz et al, 2010;Jiruska et al, 2010a).…”
Section: Fast Ripples and The Epileptic Hippocampus: The Out-of-phasementioning
confidence: 99%
“…Moreover, experiments performed in both in vitro and in vivo preparations indicate that fast ripples do not depend on inhibitory transmission as they are easily observed during GABA A receptor blockade and, indeed, they appear to represent the synchronous firing of principal (glutamatergic) neurons (D'Antuono et al, 2005;Engel et al, 2009;Bragin et al, 2011). The possibility that fast ripples emerge as the result of loss of synchronization during jittery, out-of-phase burst firing of principal cells in the epileptic hippocampus has been proposed (Foffani et al, 2007;Ibarz et al, 2010).…”
Section: Role Of Gaba a Receptors In Neuronal Network Oscillationsmentioning
confidence: 99%
“…HFOs are categorized as ripples and fast ripples (250 -500 Hz) (Jefferys et al 2012a), and it has been proposed that ripples represent inhibitory postsynaptic potentials (IPSPs) generated by principal neurons entrained by synchronously active interneuron networks (Ylinen et al 1995), whereas fast ripples reflect synchronous in-phase or out-ofphase firing of abnormally active (Jefferys et al 2012) principal cells, thus being independent of inhibitory neurotransmission (Dzhala and Staley 2004;Foffani et al 2007;Engel et al 2009;Ibarz et al 2010;Bragin et al 2011). According to the findings reported by Avoli and colleagues (Levesque et al 2012), low-voltage fast activity seizures are mainly associated with increased ripple rates, whereas hypersynchronous seizures are mostly accompanied by fast ripples.…”
Section: Seizure Onsetmentioning
confidence: 99%